2021
DOI: 10.1002/pbc.29426
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography profiles in critically ill children with multisystem inflammatory syndrome

Abstract: Objectives: To describe critically ill children's coagulation profile with the multisystem inflammatory syndrome (MIS-C) related to coronavirus. Study design: Single-center, observational study at a tertiary, pediatric intensive care unit (PICU) in children aged 1 month to 18 years. Measurements and main results: Sixteen children, with a median age of 5.4 years (interquartile range [IQR] 2.1, 11.75), 56% female, admission Pediatric Logistic Organ Dysfunction-2 (PELOD-2) score of 3.5 (IQR 2, 5), and median PICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Ankola et al demonstrated that patients with MIS-C had evidence of hypercoagulability on thromboelastography (TEG); their TEG profiles were consistent with faster clot formation, increased clot strength, and slower fibrinolysis (72). This novel finding has been confirmed by the study of Morparia et al and provides a potential unique biomarker to distinguish the risk for thrombosis in the pediatric patients (73).…”
Section: Discussion Pathophysiologymentioning
confidence: 90%
“…Ankola et al demonstrated that patients with MIS-C had evidence of hypercoagulability on thromboelastography (TEG); their TEG profiles were consistent with faster clot formation, increased clot strength, and slower fibrinolysis (72). This novel finding has been confirmed by the study of Morparia et al and provides a potential unique biomarker to distinguish the risk for thrombosis in the pediatric patients (73).…”
Section: Discussion Pathophysiologymentioning
confidence: 90%
“…In pediatric MIS-C, a single center report (n = 30) showed patients had evidence of hypercoagulability on TEG R but similarly did not demonstrate any symptomatic thrombotic event or major bleeding (86). In a single center cohort (n = 22) of pediatric patients with acute COVID-19 and MIS-C, TEG R uncovered a pattern of accelerated clot formation and increased clot strength in a subset of children and unlike the previous reports this cohort included two patients with significant thrombotic complications (87).…”
Section: Vet Impact During Covid-19mentioning
confidence: 80%
“…MIS-C patients are subjected to a hyperinflammatory state leading to a higher risk of thrombotic manifestations by the activation of the coagulation system, especially in the event of a more severe clinical course [ 7 , 8 , 10 , 50 , 51 , 52 ]. The incidence of TEs ranges from 1 to 6.5% in the largest series [ 3 , 10 , 21 , 50 , 51 ] and their occurrence is more frequent among adolescents, accounting for 7–19% in patients older than 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported coagulation abnormalities are the elevation of D-dimer and fibrinogen levels [ 3 , 4 , 6 ]. In addition, the prothrombotic state seems to be promoted by high clot strength and a consequent slowing of the fibrinolytic process [ 7 , 8 ]. To prevent TEs, the use of antiplatelets and/or anticoagulants has been recommended, largely based on experience in similar pediatric conditions, specifically Kawasaki disease and myocarditis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%